The Digital Circular Economy: How AI and Blockchain are Redefining Global Sustainability Standards. Examining Technological Innovations in Global Circular Economy Systems (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
The global environmental crisis caused by population growth, waste, and resource exploitation demands a shift towards a more sustainable economic system. This study examines the role of Artifical Intelligence (AI) and Blockchain technological innovations as solutions in strengthening the implementation of the circular economy at the global level. Using qualitative methods through literature studies and focused group discussions, the resuts show that AI can optimize waste management and supply chains efficiently, while Blockchain increases transparency and accountability through secure digital recording. The integration of the two forms the Digital Circular Economy (DCE)-an innovative solution that promotes resource efficiency, data fairness, and global carbon footprint reducation. DCE is a strategic step toward creating new sustainability standards that are smart, transparent, and future-oriented.